Disturbances as factor of complication of operative situation - Lavnichenko, О. V. (Honor and Law, 2019)
The problems concerning the definition of disturbances as the mass negative phenomenon, range of measures conducted by the civil authorities, the Internal Affairs agencies and the Interior Troops agencies depending on the stages of agitations and mass disturbances are considered.